Creativity Innovation Collaboration and Knowledge Based Economy As Strategic Management to Enhance Creative Industry in Indonesia - Alanudin, Dian; Gidry Abdurrazak , Muhamad; Yakoob Khan , Sikander (Action Research Literate, 2024)
Indonesia has a rich cultural diversity which provides profuse resources for its creative industry. The purpose of this paper is to find solutions for how to minimize the lack of capital and investment in Indonesia's creative industry. The primary objective is to find solutions to support and maintain the growth of our varied creative industry and minimize lack of capital and investment. This research focuses on the creative industry in Indonesia, SME and startups which are limited and related to only creative industry. The research methodology used is qualitative by observation and interviews. The results of the study show from observation and interviews, this study found that there are 7 components that can be implemented as a strategic solution to the current condition problem. Using PESTEL, Porter's Five Forces, Fishbone diagrams to find root causes, and Stakeholder analysis to identify key players to develop a sustainable competitive advantage (SCA) activity map. From PESTEL's analysis, we can see that the Indonesian government already has a policy to support the creative industry under the Creative Economy Fund/Creative Industry Fund for pre-startups.